PP.03.29: VISIT TO VISIT BLOOD PRESSURE (BP) VARIABILITY AND CAROTID ATHEROSCLEROSIS IN RENAL TRANSPLANT PATIENTS. (June 2015) - Leonardis, D.; Tripepi, R.; Provenzano, F.; Mafrica, A.; D'Arrigo, G.; Tripepi, G.; Bellantoni, M.; Zoccali, C.; Mallamaci, F.
Abstract : Objective: Visit-to-visit BP variability is an independent predictor of cardiovascular events in patients with essential hypertension, chronic kidney disease and end stage kidney failure. To date, no study specifically looked at the relationship between visit-to-visit BP variability and surrogate endpoints of cardiovascular risk in renal transplant patients. Design and method: In this study, we investigated the relationship between long term visit-to-visit BP variability (expressed in terms of standard deviation calculated throughout 6 consecutive visits at 1–2 months of interval) and a surrogate biomarker of atherosclerosis [intima media thickness (IMT) measured by eco-color Doppler study of the carotid arteries]. We studied 177 renal transplant patients with a mean age of 46 ± 12 years [Males: 68 %; Diabetics: 8%; Smokers: 6%, estimated glomerular filtration rate (eGFR): 56 ± 20 ml/min/1.73 m2]. The large majority of patients (87%) were on anti-hypertensive treatment. Results: Visit-to-visit BP variability was 11 mmHg for systolic BP (delta SBP) and 7 mmHg for diastolic BP (delta DAP). On univariate analysis, both systolic (r = 0.33, P < 0.001) and diastolic (r = 0.16, P < 0.03) BP variability were directly related to IMT and these relationships held true in multivariate linear regression models (delta SBP-IMT, beta = 0.21, P = 0.005; delta DAP-IMT, beta = 0.15, P = 0.03) adjusting for average systolic and diastolic BPs across the follow-up as well as for other potential confounders (age, gender, smoking, diabetes, cholesterol, albumin, C-reactive protein, 24 h urinary protein, eGFR and anti-hypertensive treatment). Conclusions: Visit-to-visit BP variability is an independent correlate of carotid atherosclerosis in renal transplant patients. Randomized, placebo controlled, clinical trials testing the potential effect of anti-hypertensive drugs specifically affecting BP variability are needed to clarify the nature (causal/non causal) of the relationship between visit-to-visit BP variability and IMT in renal transplant patients.